Atherosclerosis Early Detection In Type 1 Diabetes Mellitus - Seprian Widasmara; Novi Kurnianingsih; Mohammad Saifur Rohman; Anna Fuji Rahimah (Heart Science Journal, 2022)
Atherosclerosis continues to be a significant consequence in type I diabetes mellitus (T1DM). Cardiovascular disease, caused by accelerated atherosclerosis, is the leading cause of illness and often premature death in patients with T1DM. Risk management is critical. Patients with T1DM who are at an increased risk include those who are less than 10 years old at the time of diagnosis, have a longer history of diabetes, have microvascular problems, or have several risk factors. It is frequently difficult to evaluate vascular hazard and the degree of atherosclerosis on an individualized level, especially early on.